2017
DOI: 10.5116/ijme.5a2d.16a3
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical symptoms and depression among medical students in Bahrain

Abstract: ObjectivesTo examine the association between depression and physical symptoms among medical students in Bahrain. Methods  The present study employed a cross-sectional design.  A total of 160 students were recruited, 41.3% were male and 58.8% female, using a convenience sampling approach. Participants completed the validated Patients Health Questionnaires (PHQs) in which they provided information about demographics, physical symptoms, and depression. Results were considered significant if p <0.05. ResultsNearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
4
2
2
Order By: Relevance
“…It was observed that 11.1% of students with depression needed regular use of medications to regulate the sleep-wake cycle, while only 4.6% of students without depressive symptoms use sleepinducing medications. This data contrasts with other studies in the literature, in which depression was associated with the presence of sleep disorders (PAN et al, 2016;ABDELAZIZ et al, 2017). It is possible that the greater use of sleep-inducing medications in the group of students with depression may be responsible for the lack of association between sleeping hours and major depression.…”
Section: Discussioncontrasting
confidence: 94%
“…It was observed that 11.1% of students with depression needed regular use of medications to regulate the sleep-wake cycle, while only 4.6% of students without depressive symptoms use sleepinducing medications. This data contrasts with other studies in the literature, in which depression was associated with the presence of sleep disorders (PAN et al, 2016;ABDELAZIZ et al, 2017). It is possible that the greater use of sleep-inducing medications in the group of students with depression may be responsible for the lack of association between sleeping hours and major depression.…”
Section: Discussioncontrasting
confidence: 94%
“…This systematic review and meta-analysis aimed (1) to pool results of the global prevalence of FEDs symptoms in medical students, and (2) to assess whether this prevalence varies as a function of sex, age, BMI, or culture. Given that reported stress levels and mental health symptoms have been increasing slightly over the past years among students [30][31][32], we hypothesized to find an increased prevalence of FEDs symptoms in our target population. Additionally, we hypothesized that prevalence of FEDs symptoms would be higher among females, students with higher BMI and those from Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sleep quality and depressive symptoms among medical students has already been a focus of past literature [ 16 18 ]. Sleeping problems in general may be a predictor of depression, as the authors of a study among medical students in Bahrain found: students reported somatic symptoms rather than psychological problems [ 19 ]. In the present study, poor sleep quality and consumption of sleeping pills, as well as prolonged sleep latency and the female gender had the greatest association with the occurrence of depressive symptoms [ 20 ].…”
Section: Discussionmentioning
confidence: 99%